Regression Analysis of The National Cyber Security Index In The Southeast Asia Region - Adityan Wisnu Yuda Prasetya; Bambang Suhardjo; Rinaldy Munir (Asian Journal of Social and Humanities, 2024)
In the current era of the Industrial Revolution 4.0, information and communication technology is rapidly developing in all sectors. In the matrix of non-military defense implementation, technology is one of the dimensions that influence the achievement of a country's general defense policy. Technological development does not always have a positive impact. Cyber threats and attacks are an example of the negative impact in technological development. In the "Cyber Defense Guidelines," national cyber security is defined as all efforts to maintain the confidentiality, integrity, and availability of information and all its supporting facilities at the national level, which are cross-sectoral in nature. According to data from the National Cyber Security Index (NCSI) survey agency, a country's National Cyber Security Index (Y) is measured based on 12 indicators, including: cyber security policy development (X1), cyber threat analysis and information (X2), education and professional development (X3), contribution to global cyber security (X4), protection of digital services (X5), protection of essential services (X6), e-identification and trust services (X7), protection of personal data (X8), cyber incident response (X9), cyber crisis management (X10), fight against cybercrime (X11), and military cyber operations (X12). In this study, a regression analysis will be conducted on the 12 indicators of the National Cyber Security Index against the Total Assessment of the National Cyber Security Index (Y) in Southeast Asia, so that the type of equation in the regression analysis can be identified.